Hubungan karakteristik klien, keluarga dan stigma dengan dukungan keluarga pada klien Harga Diri Rendah. - Daryanto Daryanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
The research goal was identified correlation between client and family characteristic, stigma with family support. This research study was descriptive design by using cross sectional as a disign, took place at Mentally hospitallyProvince ofJambi in April to Mei 2007. Porposive sampling for selected of 80 sampel each for clien and family has been choosen 160 subjects totally with inclusion criteria. All instruments has been proven was valid (r>0,361. Reliability for self esteem inventory ( r=0,931), knowledge (r=0,843), Stigma ( r=0,889), Family support (r=0,939). The reseach result revealed that there were a correlation age (PV 0,004), stigma (0,011) and emotional support. There were a correlation between age ( P 0,017), education (PV 0,010), stigma (PV 0,002) and informational support. There was a correlation between education (PV 0,008) and instrumental support. There were a correlation between knowledge (PV 0,049), stigma (PV 0,019) and apraisal support. Recomendation to the hospital manager at Mentally hospitalprovince ofJambi was hope to facillitate training program, make a self help groups for the family, health education of stigma for nurse and public in order to get well family support. The family supposed to more attention, cared for client as long as in mentally hospital, accepted, acknowledged and praised attitudes of the client. In the future research  need to know nurse support and social stigma for low self esteem client.           Key word :  Client and family characteristic, stigma, family support, low self esteemReferences